Sentence condemning the former president of Peru for violations of human rights (Società e diritti, 2017)
There is an empirical relationship between state and type of protection or violation of human rights a constitutional and democratic state of law there is a greater guarantee of protection of human rights than in an authoritarian and dictatorial state. This last situation is attributed to the ex President of Peru, Alberto Fujimori, who governed from 1990 to 2000; Having been sentenced by the Peruvian courts for human rights violations, to 25 years of imprisonment. It is the only case in Latin America where a former president is in prison for violation of Human Rights. This paper describes the socio-political conditions in which context human rights were violated; It analyses the factual and legal reasoning of the judges, contained in the sentence vs. ex-president Alberto Fujimori.Key words: Human Rights, Authoritarian State,Latin America;Resumen